Comparative analysis of the epidemiological profile of non-melanoma skin cancer in Brazil, Northeast and Maranhão, in the 2015-2019 period (Research, Society and Development, 2021)
The accumulation of mutations that results in disordered cell growth is called cancer. This disease affects thousands of people worldwide and its main type is skin of non-melanocytic origin, which includes basocellular and spinocellular carcionomas. Its main risk factor is unprotected exposure to sunlight. Thus, since Brazil is a country with a mostly tropical climate, it receives a significant amount of radiation, making its residents more susceptible to the damage of a prolonged photoexposure, especially in the northeast region. The objective of this work was to carry out an epidemiological analysis of the last five years in Maranhão, in the Northeast and in Brazil on non-melanoma skin cancer, through observational analytical cross-sectional study, qualitative and quantitative, and data were collected from the available oncology panel at DATASUS in the period from 2015 to 2019. The results showed that skin cancer is the most incident and prevalent in Brazil, mainly in the population equal and older than 70 years, with Rio Grande do Sul being the most affected state in Brazil and the Rio Grande do Norte, the Northeast. It is more prevalent in the female population. The health campaign "December Orange" is today the main strategy for the prevention of skin cancer in Brazil.